Islamic Butcher Shop Read as a Refugee Novel - Kim, Jooyoung (Archīum Ateneo, 2024)
In 1950, a civil war broke out between the North Korean army (with the support of China and the Soviet Union) and South Korea (supported by the US and UN forces). Son Hong-gyu’s novel Islamic Butcher Shop (2010) begins with the background of Turkish and Greek soldiers—among the UN troops from 16 countries, including the US military. They have not returned to their home countries but remain in Korea and live with the trauma of war. Islamic Butcher Shop is a novel emphasizing images of refugees based on multicultural perspectives. The boy, who is the central figure and narrator of this novel, is not given a name. He is not categorized as a “citizen” under the family register system of Korea, but he is stuck somewhere between being a Korean national and not having citizenship. So why did this novel have to bring refugees to the scene of Korean society in the 1980s? Korean society tends to see refugees as unfamiliar because of a single-race nationalism based on the ideology of pure blood. After South Korea joined the Refugee Convention in 1992, the number of refugee applicants increased, causing South Koreans to be more aware of the refugee issue. Koreans tend to be cautious about not only refugees but also immigrants. This is partly due to the fact that the narrative of the nation-state emphasizes homogeneity and conceals the uniqueness exhibited during modernization after the postcolonial period in Korea. In this situation, Islamic Butcher Shop, by portraying the lives of refugees against the backdrop of the trauma of war and not of political or economic migration, serves as a wake-up call for the distorted ideology of pure blood and nationalism. That is, the novel dismantles stereotypes based on race, religion, or social class.